Is Training With Gym Machines Safe After Hip Arthroplasty?—An In Vivo Load Investigation - Haffer, Henryk; Bender, Alwina; Krump, Alexander; Hardt, Sebastian; Winkler, Tobias; Damm, Philipp (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Training with gym machines is one of the most popular physical activities after total hip arthroplasty (THA). However, to date, there are no evidence-based recommendations for physical activity after THA, worldwide. The aim of the study is to evaluate the in vivo hip joint loads during exercises on four widely used gym machines in order to provide a source for an evidence-based patient counselling for arthroplasty surgeons. Methods: The in vivo hip joint loads in seven patients (59.6 ± 6.4 years, 28.6 ± 2.1 kg/m2) with instrumented hip implants were assessed. The resulting force (Fres), bending moment (Mbend), and torsional moment (Mtors) were evaluated during the training on leg curl/leg extension machines (loads: 20, 30, and 40 kg), leg press machine [backrest: 10°, 30°, and 60°; load: 50, 75, and 100%BW (bodyweight)], and a rope pull machine (abduction/adduction/flexion/extension; each ipsi- and contralateral; load 10 kg). These loads were compared with the loads during walking on treadmill at 4 km/h (median peak values: Fres 303%BW, Mbend 4.25%BWm, and Mtors 2.70%BWm). Results: In each of the four performed exercises with a total of 23 different load conditions or exercise modes analyzed, a significantly lower or not different load was detected with respect to Fres, Mbend, and Mtors measured while walking with 4 km/h. Nevertheless, Fres and Mbend demonstrated a trend to increased loading during the ipsilateral monopod standing rope pull exercises hip flexion, extension, and abduction. Conclusion: Based on our investigation, we assume that the investigated gym machines and external loads can be considered mainly as low-impact sports (with some exceptions) and thus as safe physical activity after THA. Due to the fact that the examinations were conducted in the mean 17.4 months after THA, the applicability of the results to the immediate postoperative period is limited.